2022
DOI: 10.1039/d2tc01484j
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study of thePnmaandRmphases of Sb2S3, Bi2S3, and Sb2Se3

Abstract: We report a comparative theoretical study of the Pnma and R3̄m phases of Sb2S3, Bi2S3, and Sb2Se3 close to ambient pressure and show that both phases of Sb2S3 may coexist up to moderate applied pressures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 100 publications
0
6
0
Order By: Relevance
“…For instance, using them, one can control a reversible semiconductor-to-metal transition in MoTe 2 thin films 79 or can reversibly tune an electrical resistance in two-dimensional MoS 2 junctions to enhance a photovoltaic effect. 80 High-pressure phases and effects can also be implemented in thin films, 81 since due to epitaxial misfit strains a stress of several GPa or higher can be easily generated. 82 For example, a high-pressure polymorph of GeCu 2 O 4 , which is normally stable above 4 GPa, was stabilized in epitaxial films deposited on MgAl 2 O 4 substrates.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, using them, one can control a reversible semiconductor-to-metal transition in MoTe 2 thin films 79 or can reversibly tune an electrical resistance in two-dimensional MoS 2 junctions to enhance a photovoltaic effect. 80 High-pressure phases and effects can also be implemented in thin films, 81 since due to epitaxial misfit strains a stress of several GPa or higher can be easily generated. 82 For example, a high-pressure polymorph of GeCu 2 O 4 , which is normally stable above 4 GPa, was stabilized in epitaxial films deposited on MgAl 2 O 4 substrates.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, theoretical calculations of the tetradymite structure in all group-15 sesquichalcogenides has shown that they can be arranged in a diagram and that all stable tetradymite sesquichalcogenides are located in a small region of the diagram. 67,89 The multicenter bonding character of some bonds in β-As 2 Te 3 was already noted by Yu et al , 39 who also justified the large anharmonicity of this unconventional bond. Further support for the presence of multicenter bonding in β-As 2 Te 3 already at low pressure is shown by the large values of the average optical dielectric constant, ε ∞ , and Born effective charges of β-As 2 Te 3 when compared to those of α-As 2 Te 3 (Fig.…”
Section: Resultsmentioning
confidence: 65%
“…It is worth commenting that a competitivity of the tetradymite R% 3m phase at room pressure with the supposedly more stable Pnma phase has been recently found in Sb 2 Se 3 . 67 These results show that it is worth exploring both As 2 Te 3 and Sb 2 Se 3 , since they are sesquichalcogenides in which the R% 3m phase is competitive at room pressure, despite it is not the common phase observed at room pressure, unlike in Sb 2 Te 3 , Bi 2 Te 3 , a-and Bi 2 Se 3 .…”
Section: Hp-xrd Measurementsmentioning
confidence: 85%
See 1 more Smart Citation
“…However, problems of the rare earthly presence of most of the materials and their high toxicity (especially of Cd and Zn) have diverted research attention to the less toxic chalcogenides. These chalcogenides, such as Sn(S/Se), Sb 2 (S/Se) 3 , Bi 2 S 3 , and CuSb(S/Se) 2 , have recently demonstrated promising results in thin film solar cell applications [2,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%